Comparison of the Effectiveness of Play Therapy and the Integration of Play Therapy with Parent Management Training on Anxiety in Children with Siblings Who Have Special Needs - Akbarian, Sakineh; Abdi, Hassan; Taher, Mahboobe (Mental Health and Lifestyle Journal, 2025)
Anxiety disorders represent one of the most prevalent forms of psychological pathology during childhood. Therefore, the present study aimed to compare the effectiveness of play therapy and the integration of play therapy with parent management training on anxiety in children who have a sibling with special needs. The research employed a quasi-experimental design using a pretest–posttest format with control and experimental groups. The statistical population included all families with children with special needs enrolled in exceptional schools in Ramian County. A total of 37 participants were selected purposefully based on the study's inclusion and exclusion criteria (12 participants in the play therapy group, 13 in the integrated intervention group, and 12 in the control group). The data collection instrument was the Children’s Symptom Inventory-4 (CSI-4) developed by Sprafkin and Gadow. Data analysis was conducted using one-way ANOVA and Bonferroni post hoc test. The statistical analysis software used was SPSS version 27. The results indicated that, based on the differences in mean scores, anxiety scores significantly decreased from pretest to posttest in both experimental groups and from pretest to follow-up only in the group that received the integrated intervention (play therapy and parent management training) (p ≤ .001). Moreover, a significant difference was found in the follow-up phase between the integrated group and the play therapy group (p ≤ .001). It appears that both play therapy and the integration of play therapy with parent management training are effective in reducing anxiety in children who have a sibling with a disability.